Inactivation of vitamin B6 by hydroxyurea in Aspergillus culture media - S Foster; P M MIRABITO (Fungal Genetics Reports, 1998)
We found that sublethal levels of Hydroxyurea (HU), an inhibitor of ribonucleotide reductase, inhibited the growth of pyroA4 mutants of Aspergillus nidulans. Growth inhibition increased with the age of the HU-containing medium, and was remediated by supplementation with additional vitamin B6, indicating that HU leads to the inactivation of vitamin B6. HU inactivated vitamin B6 in the presence or absence of media components. These results demonstrate a direct affect of HU on vitamin B6, and they complicate the interpretation of results from experiments involving HU and fungal strains auxotrophic for vitamin B6.